Gestalt ontology in international relations: The case of European integration - ÇAKIR, ARMAĞAN EMRE (My University, 2009)
This article proposes a new interdisciplinary perspective in international relations (IR). It suggests that contributions from perception studies can help us reconceptualize some elements of IR. Specifically, the article takes up the concept of Gestalt and applies it to European integration. The Gestalt laws and phenomena demonstrated by European integration can be identified in other examples of regional integration, as well as in various international organizations, or alliances. They also provide insight into other features of IR, such as the international order. The Gestalt approach per se may contribute to the development of a psychological constructivist theory of IR. © 2009 International Studies Association.
Keywords: European Union; Gestalt; Integration theory; Psychological constructivism